2022
DOI: 10.3389/fpsyg.2022.947189
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoint of operating room nurses about factors associated with the occupational burnout: A qualitative study

Abstract: BackgroundOccupational burnout is a mental health problem that among nurses may lead not only to physical and psychological complications, but also to a decrease in the quality of patient care. Considering the stressful nature of surgery, operating room nurses may be at a greater risk. Therefore, the present study aimed to identifying factors associated with the occupational burnout from the perspective of operating room nurses.Materials and methodsThis qualitative study was conducted in Iran in 2021 using con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 46 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…The results of the present study are consistent with studies conducted by ZareKhafri et al in Iran ( ZareKhafri et al, 2022 ) and Ogden et al in America ( Ogden et al, 2005 ). In this regard, the results of qualitative studies in Iran have shown that discrimination exists as a concern among nurses for inter-professional cooperation ( Valizadeh et al, 2015 ; Teymoori et al, 2022 ). In addition, discrimination unconsciously leads to aggressive behaviors that are destructive to the goals of the organization.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study are consistent with studies conducted by ZareKhafri et al in Iran ( ZareKhafri et al, 2022 ) and Ogden et al in America ( Ogden et al, 2005 ). In this regard, the results of qualitative studies in Iran have shown that discrimination exists as a concern among nurses for inter-professional cooperation ( Valizadeh et al, 2015 ; Teymoori et al, 2022 ). In addition, discrimination unconsciously leads to aggressive behaviors that are destructive to the goals of the organization.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the work in the operating room (OR) and Surgical Department provides nurses with a more controlled and structured environment [50], which contributes to better stress management. In these departments, nurses are part of a well-coordinated team that follows a set routine and protocol.…”
Section: Relationship Between Areas Of the Hospital And The Impact Of...mentioning
confidence: 99%
“…Despite this, redeployment can be a damaging experience for staff, increasing risk of stress-related illness, mismanagement and negatively affect staff retention, particularly among those who do not feel psychologically safe or well supported by managers ( Galura 2020 , Willis et al 2021 ). For TPs, an already scare resource at a high risk of negative occupational mental-health consequences, this risk is further compounded ( Cumpsty-Fowler & Saletnik 2021 , Esmaeil et al 2022 ). This creates a danger for managers of a workforce at increased risk of illness and demotivation, undermining the organisation’s ability to recover and adversely affecting their ability to provide surge capability in the time of most pronounced need.…”
Section: Adaptive Capacity (Ac)mentioning
confidence: 99%